2019
DOI: 10.46586/tches.v2019.i4.243-290
|View full text |Cite
|
Sign up to set email alerts
|

The Interpose PUF: Secure PUF Design against State-of-the-art Machine Learning Attacks

Abstract: The design of a silicon Strong Physical Unclonable Function (PUF) that is lightweight and stable, and which possesses a rigorous security argument, has been a fundamental problem in PUF research since its very beginnings in 2002. Various effective PUF modeling attacks, for example at CCS 2010 and CHES 2015, have shown that currently, no existing silicon PUF design can meet these requirements. In this paper, we introduce the novel Interpose PUF (iPUF) design, and rigorously prove its security against all known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(79 citation statements)
references
References 19 publications
2
77
0
Order By: Relevance
“…3) Resistance against PUF modeling mechanisms: SVM, LR, and CMA-ES have been shown to be effective in attacking the arbiter-PUF and its derivatives (XOR-PUF, Feed-Forward PUF, etc) with high accuracy [19], [20]. Accordingly, this set of results investigates the resiliency of our proposed method against these modeling mechanisms.…”
Section: A Experimental Resultsmentioning
confidence: 98%
“…3) Resistance against PUF modeling mechanisms: SVM, LR, and CMA-ES have been shown to be effective in attacking the arbiter-PUF and its derivatives (XOR-PUF, Feed-Forward PUF, etc) with high accuracy [19], [20]. Accordingly, this set of results investigates the resiliency of our proposed method against these modeling mechanisms.…”
Section: A Experimental Resultsmentioning
confidence: 98%
“…Hence, total GE for 128‐bit CRC PUF is 1156. Interpose PUF proposed in [13] consists of one n ‐bit arbiter PUF and one ( n + 1) bit arbiter PUF.…”
Section: Simulation and Results Analysismentioning
confidence: 99%
“…In other words, the MARPUF is more resistant to ML attacks. We also compared the proposed MARPUF with other PUF schemes like CRC PUF [12], interpose PUF [13] , and Wang et al PUF [16] to evaluate the hardware cost and it is observed from Table 3 that the proposed MARPUF has the edge over the said PUF designs. Furthermore, MARPUF requires two clock cycles to generate the output as PUF response, which is higher than the conventional PUF like RO PUF and arbiter PUF designs, as MARPUF involves two rounds of operation.…”
Section: Discussionmentioning
confidence: 99%
“…Our above GeniePUF architecture has been implemented on Xilinx Zynq FPGA with a so-called Interpose PUF or iPUF [28] as its underlying PUF. Interpose PUFs are constructed from Arbiter PUFs of variable length, and consist of several parallel layers of these Arbiter PUFs, similar to the well-known XOR Arbiter PUF architectures [45].…”
Section: Practicality and Performance Figures Of Our Constructionmentioning
confidence: 99%
“…Starting with the practical and implementational side, further optimization of our logical Erasable PUFs together with prototyping in FPGAs and ASICs seems a worthwhile endeavour. Other Strong PUFs than the iPUF [28] can be used in connection with the generic GeniePUF technique. On the theory side, our novel definitional framework will first of all hopefully spark a new style of easily acccessible, intuitive PUF-definitions in follow-up works.…”
Section: Summary and Future Workmentioning
confidence: 99%